3-Hydroxyanthranic acid inhibits growth of oral squamous carcinoma cells through growth arrest and DNA damage inducible alpha - Guifang Gan; Xinxia Zhou; Qiaoping Zheng; Xianfu Gao; Xu Chen; Han Zhang; Jinghao Liu; Zhaopeng Shi; Fuxiang Chen (Translational Oncology)
Objectives: The specific role of 3-hydroxyanthranilic acid(3-HAA) in oral squamous cell carcinoma (OSCC) remains unclear. This study investigated the roles of 3-HAA in OSCC and the underlying mechanism. Materials and methods: The effects of 3-HAA on OSCC were examined using CCK-8, colony formation, EdU incorporation assays and xenograft mouse model. The underlying mechanisms were investigated with RNA-seq, apoptosis array and cell cycle array. Short hairpin RNAs (shRNAs) were used to knockdown the expression of growth arrest and DNA damage inducible alpha (GADD45A) in OSCC cells. CCK-8 and xenograft mouse model were employed to elucidate the role of GADD45A. The binding sites between GADD45A and Yin Yang 1(YY1) were determined using luciferase reporter assay. Results: 3-HAA was selectively down-regulated in OSCC patients and the decreasing level intensified with pathological progression. Higher expression of kynurenine 3-monooxygenase (KMO) and kynureninase (KYNU), which can increase the content of 3-HAA, was associated with poorer prognosis of OSCC patients. Exogenous 3-HAA hampered growth of OSCC cells both in vitro and in vivo. 3-HAA induced growth arrest, G2/M-phase arrest, and apoptosis of OSCC cells. RNA-seq indicated that 3-HAA significantly increased GADD45A expression. 3-HAA promoted transcription of GADD45A by transcription factor YY1. Knockdown of GADD45A significantly reversed 3-HAA-induced growth inhibition of OSCC cells in vivo and in vitro. Discussion: 3-HAA induced apoptosis and cell cycle arrest of OSCC cells via GADD45A, indicating that 3-HAA and GADD45A are potential therapeutic targets for OSCC.